Trapezoidal osteochondral autologous plug singleblock graft for treating chondral lesions of the knee: clinical and functional medium-term results in an observational study (Clinics, 2012)
OBJECTIVE: To evaluate the clinical and functional results of autologous trapezoidal plug single-block grafts fixed with absorbable chondral darts in patients with osteochondral knee lesions of varying sizes. METHODS: Twenty-five patients underwent surgery from February 2000 to June 2008. Seventy-two percent of the patients were male, and the mean age was 29 years. RESULTS: The right side (56%) and the medial condyle (92%) were most affected. The lesions had an average area of 5.28 cm², and the mean follow-up was 59 months. All of the variables other than instability showed significant improvements (p